Targeting development : critical perspectives on the millennium development goals - Black, Richard, 1964 August 10-; White, Howard, 1960- (Routledge studies in development economics, 2004)
The Millennium Development Goals accepted by the UN in 2000 are, along with the targets set by the OECD in 1996 the subject of this expertly written book.